Foundation fieldbus : from theory to practice - Viegas, Vítor (2000)
This paper describes the main characteristics of the Foundation Fieldbus (FF) technology considering both communication levels, namely H1 and H2, which have bit rates of 31.25 K and 100 Mbit/s, respectively. Several details about the physical layer, communication stack and user layer will be highlighted. Topics related with the configuration of instruments, as well as the design and implementation of supervision software, based on a LabVIEW interface, will be presented. A pilot plant that includes temperature, pressure, level and flow variables will be used to test and validate the capabilities of FF systems. Experimental results will be analyzed, their meaning discussed and the overall performance evaluated.